(untitled) (Journal of actual problems of jurisprudence, 2019)
This article examines the nature, types and structure of environmental risks in the mineral resources. It was determined that the variety of risks associated with the environment described in a single term - environmental risks. Under the environmental risk is commonly understood in advance of the estimated probability of occurrence and severity in a given anthropogenic interference with the natural environment of such violations, which may be unfavorable to the continued functioning of ecological systems and the existence of a direct field of human impact, and beyond. It is shown that the work carried out in the mineral resources have a significant impact on the environment. Based on the research the author gives a complete definition of environmental risk, formulated its basic characteristics and structural elements Key words: environmental risks, market economics, geology, subsoil insurance.